2017
DOI: 10.2139/ssrn.3065703
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Growth Effects of Fiscal Policy: A Bayesian Model Averaging Approach

Abstract: Motivated by the mixed evidence in previous literature, we reexamine the effects of various types of government spending and taxes, as well as overall budget surplus/deficit, on economic growth. To address the model uncertainty issue that may have plagued earlier studies we employ a Bayesian Model Averaging (BMA) approach. We use a panel data set for OECD countries for the 1990-2013 period, control for country and time specific effects, and allow for a wide range of other potential growth determinants. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…They argued that in conditions where the social rate of return is in excess of the private return of an investment, taxation policies designed to encourage investment could augment economic growth. In a relatively recent work by Arin et al (2019), the influential role of various fiscal policy measures on economic growth was affirmed. Again, the key to the subject matter of economic growth and development is the work of Sala-i- Martin et al (2004), who showed that a significantly varied number of factors influence long-term growth; most dominant among such variables include the relative price of an investment, real GDP per capita and education (primary school enrolment).…”
Section: Jfep 143mentioning
confidence: 99%
“…They argued that in conditions where the social rate of return is in excess of the private return of an investment, taxation policies designed to encourage investment could augment economic growth. In a relatively recent work by Arin et al (2019), the influential role of various fiscal policy measures on economic growth was affirmed. Again, the key to the subject matter of economic growth and development is the work of Sala-i- Martin et al (2004), who showed that a significantly varied number of factors influence long-term growth; most dominant among such variables include the relative price of an investment, real GDP per capita and education (primary school enrolment).…”
Section: Jfep 143mentioning
confidence: 99%
“…The results under both approaches are identical. We choose to present the method and the results based on the above computational scheme as this is the standard practice in Bayesian literature (see for instance, Arin et al (2019) and Steel (2020)).…”
Section: Mcmc Sampler Algorithmmentioning
confidence: 99%
“…Batini et al [7] find that in order to meet fiscal constraints, increasing taxes has a less adverse effect on output than cutting government spending. In addition, Arin et al [8], using Bayesian model averaging, find that productive public spending has a positive effect on output, while top corporate tax rates have a negative effect, and fiscal variables with no robust effect on output include top income tax rates, government consumption, and distortionary taxes.…”
Section: Theoretical Economics Lettersmentioning
confidence: 99%